2000
DOI: 10.1002/(sici)1097-0061(20000330)16:5<463::aid-yea535>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic and aerobic batch cultivations of Saccharomyces cerevisiae mutants impaired in glycerol synthesis

Abstract: Glycerol is formed as a by-product in production of ethanol and baker's yeast during fermentation of Saccharomyces cerevisiae under anaerobic and aerobic growth conditions, respectively. One physiological role of glycerol formation by yeast is to reoxidize NADH, formed in synthesis of biomass and secondary fermentation products, to NAD + . The objective of this study was to evaluate whether introduction of a new pathway for reoxidation of NADH, in a yeast strain where glycerol synthesis had been impaired, woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
80
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 0 publications
9
80
0
3
Order By: Relevance
“…3), and growth rate (Fig. 2), as is previously reported (17,18,35), whereas removal of GPD2 in the cox18⌬ background is completely growth inhibiting under aerobic as well as anaerobic conditions.…”
Section: Growth and Glycerol Production Under Anaerobic Conditions-supporting
confidence: 84%
See 1 more Smart Citation
“…3), and growth rate (Fig. 2), as is previously reported (17,18,35), whereas removal of GPD2 in the cox18⌬ background is completely growth inhibiting under aerobic as well as anaerobic conditions.…”
Section: Growth and Glycerol Production Under Anaerobic Conditions-supporting
confidence: 84%
“…These findings suggest a minor role for GPD1 in the aerobic redoxadjusting glycerol production of cox18⌬ mutants. The observation that cox18⌬ strains lacking GPD2 experience a complete growth arrest indicates that GPD2 is given a more important role for relieving the redox constraints in respiratory deficient mutants than reported for cells that are deprived of respiration due to anaerobic conditions (17,18,35).…”
Section: Resultsmentioning
confidence: 91%
“…These findings are in accordance with similar studies in S. cerevisiae, where decreases of 22 % or 46 % were found during aerobic and anaerobic conditions, respectively (Moreira dos Santos et al, 2004;Nissen et al, 2000). As expected, the m max of the gdhAdisrupted strains could be restored by supplementing glutamate to the medium and by overexpression of gdhB.…”
Section: Strainsupporting
confidence: 92%
“…1), and it is therefore possible to shift the co-factor requirements through genetic engineering. This has been demonstrated previously, and the co-factor switch successfully led to increased bioethanol production by Saccharomyces cerevisiae (Nissen et al, 2000).…”
Section: Introductionsupporting
confidence: 58%
“…Indeed, the authors suggest that the redox factor balance might be restored by a transhydrogenase activity that would interconvert NADH/NADP + and NAD + /NADPH. However, Nissen et al (2000) showed that the in vivo cofactor concentrations in S. cerevisiae probably would not allow the reaction to proceed in the desired direction. Another way that has been proposed to ameliorate problems with cofactor imbalances is expression of the aldose reductase gene from Pi.…”
Section: L-arabinose Fermentation By S Cerevisiaementioning
confidence: 99%